Development of speech activity of children using ICT - Ivashenko L. G., Rezaeva Y. A., Tarasova Y. V. (Educational environment today: development strategy, 2016)
The possibility of the use of ICT in the educational process is considered in the article. The article shows the necessity of the use of information and communication technologies in the implementation in the conditions of the federal state educational standards of new generation. According to the authors, the use of ICT in communication activities helps to improve the efficiency of work on the development of speech, to optimize the educational process, to individualize the education of children with speech underdevelopment, and also forms the success of children, increases motivation, significantly reduces the time for material absorption.
Keywords: современные образовательные технологии; мультимедийная презентация; информационно-компьютерные технологии; multimedia presentation; информационные образовательные ресурсы; modern educational technology; information and computer technologies; information educational resources